PENGADAAN BAHAN BAKU NIRA DAN NILAI TAMBAH PENGOLAHAN GULA AREN DI DESA AIR KUBANG, AIR NANINGAN KABUPATEN TANGGAMUS - Fembriarti Erry Prasmatiwi; Rusdi Evizal; Asyifa Rahmita Zahra (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Palm sugar is made from nira, the palm tree extraction. There are fewer palm trees and sugar craftsmen often feel difficulty getting palm sugar raw materials. This study aims to analyze the nira procurement and estimate the income and added value of palm sugar processing in Air Kubang Village, Air Naningan, Tanggamus Regency. There are four palm sugar craftsmen in total at the research location. The four of them become respondents for the interview in November-December 2021. This study used descriptive quantitative and Hayami value-added methods. The results revealed that nira was taken from sugar palm plants that grew naturally. Aside from that, there was no intensive cultivation of the plant even though the nira water is increasingly limited. Every day, two trees are tapped, producing 24.16 liters. The income of palm sugar craftsmen in Air Kubang Village is Rp55,620.00/day or Rp1,668,600.00/month. Palm sugar processing has an added value ratio of 57.03% or Rp1,560.69/liter of nira water.